Jan Floris de Jongh (1910 - 1988), President of IASSW 1954-1961 - Albert Riga (Social Work and Society, 2007)
Jan Floris de Jongh played an undoubtedly significant role in the development of social work within and beyond The Netherlands. Yet, he and his contributions to the field are barely known, particularly in The Netherlands. His achievements warrant much more attention given that this Dutchman was also one of the most relevant figures in the international social work community.